Needle Stick Injuries: Knowledge, Attitude, Practices (KAP) and Frequency of Hepatitis B & C among Nursing Students in Karachi (Medical Forum Monthly, 2024)
Objective: The objectives were to determine the Knowledge, Attitude, Practices regarding needle stick injuries (NSI) and frequency of Hepatitis B & C among nursing students at two tertiary care hospitals of Karachi.Study Design: Cross-sectional study.Place and Duration of Study: This study was conducted at the Department of Medicine, DMC, JPMC and Hilton Pharma, Karachi from January 2014 to June 2014. Materials and Methods: This study was carried out on NSI exposed 214 nursing students from 1st year to 4th year, visiting their respective hospitals and engaging in clinical activities. A hundred of those students who reported needle stick injuries randomly selected and screened for Hepatitis B surface antigen (HbsAg) and anti-HCV in sera.Results: Approximately thirty four percent (34%) of the students reported to have NSI one time. Out of the 214 students only 143 (66·8%) of the students were aware of the Universal Precaution Guidelines while 71 (33·2%) were unaware of it. After getting NSI only 18·2% reported it to the infection control team while 81.8% failed to report it. Of the 100 students randomly selected for screening, four tested positive for HbsAg and two tested positive for Anti-HCV.Conclusion: Allowing nursing students to practice without prior knowledge of their immune status poses a major risk of acquiring hazardous infections. Prior to practice, students should be ingrained with the universal precaution guidelines and screened for blood borne infections that should be followed up every year.